Cyclodextrin solubilization and complexation of antiretroviral drug lopinavir: In silico prediction; Effects of derivatization, molar ratio and preparation method. (1st January 2020) - Adeoye, Oluwatomide; Conceição, Jaime; Serra, Patrícia A.; Bento da Silva, Andreia; Duarte, Noélia; Guedes, Rita C.; Corvo, Marta C.; Aguiar-Ricardo, Ana; Jicsinszky, László; Casimiro, Teresa; Cabral-Marques, Helena
Highlights: The best CyD for LPV complexation was predicted by in silico studies. The predicted CyD was successfully synthesized (HP17-γ-CyD). LPV complexes were prepared by two methods i.e. SASD and CoEva. HP17-γ-CyD facilitated higher LPV amorphization and solubilization. SASD processing technique enhanced LPV complexation and solubilization. Abstract: Lopinavir (LPV) is currently used in combination with ritonavir for the clinical management of HIV infections due to its limited oral bioavailability. Herein, we report the application of an in silico method to study cyclodextrin (CyD) host-guest molecular interaction with LPV for the rational selection of the best CyD for developing a CyD based LPV delivery system. The predicted CyD, a (2-hydroxy)propyl-gamma derivative with high degree of substitution (HP17-γ-CyD) was synthesized and comparatively evaluated with γ-CyD and the commercially available HP-γ-CyD. All complexes were prepared by supercritical assisted spray drying (SASD) and co-evaporation (CoEva) at molar ratios (1:1 and 1:2); and afterwards fully characterized. Results indicate a higher LPV amorphization and solubilization ability of HP17-γ-CyD. The SASD processing technology also enhanced LPV solubilization and release from complexes. The application of in silico methodologies is a feasible approach for the rational and/or deductive development of CyD drug delivery systems.